Post-colonial Feminist Representations in Coetzee’s Novels - Armah, Miriam Naa Ayeley (Technium Social Sciences Journal, 2022)
As a Noble Laureate, John Maxwell Coetzee has been one of the most prominent post-colonial writers in feminist literature. This study reveals significant role of women characters in Coetzee’s novels with much attention to their representation in post-colonial Africa. This article carefully analyzes Coetzee’s selected novels; Waiting for the Barbarians (1980), Foe (1986) Age of Iron (1990) and Disgrace (1999), thus, shedding light on the treatment of African women by the colonizers and how that knowledge will help propagate the message of equality and tolerance by eliminating the evils of injustices and inequality. This study will significantly contribute to a greater awareness of women in post-colonial literature.